Paraneoplastic Cough and Renal Cell Carcinoma. (21st March 2016) - Sullivan, Stephen
Abstract : A case of patient with intractable cough due to renal cell carcinoma is reported. The discussion reviews the literature regarding this unusual paraneoplastic manifestation of renal malignancy.